Reduction of Endotoxin from Human Root Canals by Calcium Hydroxide Nanoparticles - P. Lungkapinth (2020)
© Published under licence by IOP Publishing Ltd. This study was aimed to evaluate the reduction of endotoxin using the passive ultrasonic irrigation (PUI) of calcium hydroxide nanoparticles (CHNPs) compared with the PUI of calcium hydroxide (CH) and the CH medication. Forty-seven single-root human premolars were used. The root canals were enlarged and sterilized. Escherichia coli endotoxin was inoculated into the root canals. Thirty-six root canals were assigned into three experimental groups: CHNPs irrigation, CH irrigation, and CH medication. For the irrigation groups, the PUI was activated for three min. For the CH medication, the CH was filled into each canal and incubated at 37°C for seven days. The reduction of endotoxin was evaluated by quantitative chromogenic limulus amoebocyte lysate assay. Data was analysed by Kruskal-Wallis and pairwise comparison tests, with a level of significance set at P < 0.05. The CHNPs irrigation was more effective in against endotoxin than the CH irrigation (P < 0.05). No significant difference was found between the CHNPs irrigation and the CH medication (P > 0.05). The irrigation of CHNPs could eliminate most of the endotoxin from the root canals and approximately from 300 μm of root dentin. CHNPs might be potential as an adjunctive irrigation for endotoxin removal.